From mass to motion: Conceptualizing and measuring the dynamics of industry clusters - Kim, Min Jung; Shaver, J. Myles; Funk, Russell J. (Strategic Management Journal, 2022)
Abstract Research Summary An extensive body of research examines concentration levels (i.e., “mass”) of industry clusters; however, little attention is paid to their dynamics (i.e., “motion”). Understanding cluster dynamics is important because how clusters change over time may have implications for firm strategies and outcomes that are not attributable to cluster mass alone. To advance scholarship, we derive a theoretically grounded measure of cluster motion. Applying this measure to data on establishments in the U.S. computer and semiconductor industries, we document the dynamic nature of clusters both within and across regions. We demonstrate that our measure of cluster motion is distinct from cluster mass. Furthermore, we document that regions rarely follow stylized descriptions of cluster life cycles, which underscores the importance of measuring and investigating cluster dynamics. Managerial Summary Industry clusters have been considered important for firm strategy due to their influence over organizational processes and outcomes. Therefore, many firms attend closely to how clusters change over time. However, strategy researchers have devoted relatively little attention to cluster dynamics and their implications for firms. In this study, we develop a framework for understanding cluster dynamics, including an empirical technique. We suggest that improved understanding of cluster dynamics may be useful for helping firms make better location decisions and react more appropriately to changes in clusters within which they have an established presence.